The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1116/1.568830
|View full text |Cite
|
Sign up to set email alerts
|

Study of the N–Cu(100) system

Abstract: The reaction of a clean Cu(100) surface with atomic N has been studied with low energy electron diffraction (LEED), Auger electron spectroscopy, ultraviolet photoemission spectroscopy (UPS), and x-ray photoemission spectroscopy (XPS). Atomic nitrogen, formed by electron dissociation of N2 forms a c(2×2) overlayer on the Cu(100) surface. An analysis of LEED intensity profiles averaged over constant momentum transfer indicates that the N binds in a fourfold symmetric site, 0.145 nm above the first layer of Cu at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Burkstrand et al [17] studied the c(2 x 2) structure formed by N atoms on a Cu As stated in the Introduction, the main motivation For the present study was the suggested similarity between the Fe( lOO)-c(2 x 2) surface structure and the structure of bufk Fe,N leading to the concept of "surface nitride". This assumption is nicely confirmed by the present results: Fe,N crystallizes in the fee lattice.…”
Section: Discussionmentioning
confidence: 99%
“…Burkstrand et al [17] studied the c(2 x 2) structure formed by N atoms on a Cu As stated in the Introduction, the main motivation For the present study was the suggested similarity between the Fe( lOO)-c(2 x 2) surface structure and the structure of bufk Fe,N leading to the concept of "surface nitride". This assumption is nicely confirmed by the present results: Fe,N crystallizes in the fee lattice.…”
Section: Discussionmentioning
confidence: 99%
“…There are many single layer systems like e.g. graphite/graphene [6,7], hexagonal boron nitride [8,9], boron carbides [10], molybdenum disulfide [11], sodium chlorides [12,13], or aluminium oxide [14], copper nitride [15,16] to name a few. In order to decide whether single layers are "dielectric" or "metallic" the electronic structure at the Fermi level has to be studied, where a metallic layer introduces new bands at the Fermi energy, while a dielectric layer does not.…”
Section: Single Layer Systemsmentioning
confidence: 99%
“…Bulk copper nitride (Cu 3 N) is a semiconducting material, with an experimentally determined band gap ranging between 0.8 to 1.9 eV [4]. One-atom-thick layers of copper nitride (i.e., Cu 2 N) can be grown by N + sputtering on single-crystal Cu substrates [5][6][7][8]. The insulating properties of a single atomic layer of copper nitride have been used to decouple single atomic spins from an underlying metallic Cu(100) surface for scanning tunneling microscope (STM) characterization [9].…”
mentioning
confidence: 99%